Reducing Influenza Virus Transmission: The Potential Value of Antiviral Treatment. (10th July 2021) - Hayden, Frederick G; Asher, Jason; Cowling, Benjamin J; Hurt, Aeron C; Ikematsu, Hideyuki; Kuhlbusch, Klaus; Lemenuel-Diot, Annabelle; Du, Zhanwei; Meyers, Lauren Ancel; Piedra, Pedro A; Takazono, Takahiro; Yen, Hui-Ling; et al.
Abstract: Prompt antiviral treatment has the potential to reduce influenza virus transmission to close contacts, but rigorous data on the magnitude of treatment effects on transmission are limited. Animal model data indicate that rapid reductions in viral replication after antiviral treatment reduce the risk of transmission. Observational and clinical trial data with oseltamivir and other neuraminidase inhibitors indicate that prompt treatment of household index patients seems to reduce the risk of illness in contacts, although the magnitude of the reported effects has varied widely across studies. In addition, the potential risk of transmitting drug-resistant variants exists with all approved classes of influenza antivirals. A controlled trial examining baloxavir treatment efficacy to reduce transmission, including the risk of transmitting virus with reduced baloxavir susceptibility, is currently in progress. If reduced transmission risk is confirmed, modeling studies indicate that early treatment could have major epidemiologic benefits in seasonal and pandemic influenza. Abstract : Prompt antiviral treatment has the potential to reduce influenza virus transmission from infected persons to contacts. This article reviews data addressing this topic, including resistance and the potential role of antiviral treatment in indirectly reducing seasonal and pandemic influenza burden.